The Impact of Government Policy of Presidential Instruction in 2005-2008 for Rice Policy on Food Security) - Surya Abadi Sembiring; Harianto Harianto; Hermanto Siregar; Bungaran Saragih (Forum Pasca Sarjana, 2012)
The objectives of this research is to analyze the impacts of rice policy on the food security and on producer and consumer surplus. The research used time series data. The data was a monthly time series from March 2005-September 2009. Rice policy model specification uses the simultaneous equations consisting of 15 structural equations and 11 identity equations which was estimated using Two Stages Least Squares (2SLS) method. The results show that: (1) the increase of the government purchases price of dried harvest paddy by 15 percent improve food security whereas retail rice price decrease makes producer and consumer surplus increase, and (2) the increase of the ceiling retail price of NPK fertilizer by 15 percent gave a negative impact on food security whereas retail rice price increase makes a negative effect to consumer surplus. Food security would be achieved if the government purchase on dried harvest paddy is implemented accordingly.